Optimization of Machining Parameters CNC Milling Process of Austenitic and Martensitic Stainless Steels on Surface Roughness - Mulyana, Deni; Yahya, Thoriq Zulham; Hata, Achmad; Widiatmoko, Rudy Yuni; Azmy, Ilham (International Journal of Mechanics, Energy Engineering and Applied Science (IJMEAS), 2024)
Stainless steel (SS), specifically AISI 304 and 420, was classified as austenitic and martensitic stainless steels which garnered excellent corrosion resistance (up to 650 oC) and easily to enhance mechanical properties by heat treatment. However, the machinability of these materials has not been widely studied. CNC milling process was defined as cutting process of workpiece using a rotating cutting tool which considered to improve productivity in manufacture industries. Machining parameters during CNC milling process such as cutting speed, feed rate, and depth of cut play an important role to achieve desired product with high quality. In addition, surface roughness was evaluated as pivotal factor to analyze resulted machining products of workpiece which subsequently used for direct application in vary industries. In order to study machinability of AISI 304 and 420 stainless steels, the optimization of machining parameters during CNC milling process was performed to determine their surface roughness values. The research data were analyzed by using Taguchi statistical method of S/N ratio and ANOVA. Furthermore, the results show that significant influence of machining parameters on AISI 304 austenitic stainless steel was feed rate of 82,29 %, then spindle speed of 3,75 % and depth of cut 0,63 %. Besides, for AISI 420 martensitic stainless steel, the feed rate still remains important in machining parameters of 72,93 %, then depth of cut 14.98% and spindle speed of 8.09 %. Thus, the result of this research endows more insights to know the machineability of AISI 304 and AISI 420 stainless steels.